Adoption of financial technology (Fintech) in mutual fund/ unit trust investment among Malaysians: unified theory of acceptance and use of technology (UTAUT). - Mohamad Engku Abdullah, Engku; Abdul Rahman, Aisyah; Abdul Rahim, Ruzita (International Journal of Engineering and Technology, 2018)
Disruptive innovation is related to financial technology and known as FinTech. It includesÂ design, delivery, and provider of financial investment services such as payments, real estate, investment, insurance/ takaful, deposits, financing, banking, saving and capital market. This study is about Adoption of Financial Technology (FinTech) in mutual fund/ unit trust investment among Malaysians: Unified Theory of Acceptance and Use of Technology (UTAUT). The study aims to identify the level of financial technology consumption in mutual fund/ unit trust among investors in Malaysia. The objectives of this research are: 1) to determine the level of awareness on FinTech application in mutual fund/ unit trust investment; 2) to examine the adoption of FinTechÂ in mutual fund/ unit trust investment. The objectives will explore on how FinTech changes the customers in terms of to what extent Malaysians have adopted FinTech so far. The research methodology in an adoption of FinTech service in mutual fund/ unit trust was conducted through questionnaires survey. This study assists participants in financial service management to take advantage of the opportunities offered by FinTech services. Developing the effective and systematic framework is a must for FinTech service especially in mutual fund/ unit trust investment. Implementation of FinTech will provide service improvement and transformation for investment management services in future.Â Â